MicroRNA Expression in Extracellular Vesicles from Nasal Lavage Fluid in Chronic Rhinosinusitis - Seungbin Cha; Eun-Hye Seo; Seung Hyun Lee; Kyung Soo Kim; Chung-Sik Oh; Jong-Seok Moon; Jin Kook Kim (Biomedicines, 2021)
Extracellular vesicles (EVs) are nanovesicles of endocytic origin released by cells and found in human bodily fluids. EVs contain both mRNA and microRNA (miRNA), which can be shuttled between cells, indicating their role in cell communication. This study investigated whether nasal secretions contain EVs and whether these EVs contain RNA. EVs were isolated from nasal lavage fluid (NLF) using sequential centrifugation. EVs were characterized and EV sizes were identified by transmission electron microscopy (TEM). In addition, EV miRNA expression was different in the chronic rhinosinusitis without nasal polyp (CRSsNP) and chronic rhinosinusitis with nasal polyp (CRSwNP) groups. The Kyoto encyclopedia gene and genome database (KEGG) database was used to identify pathways associated with changed miRNAs in each analysis group. Twelve miRNAs were differentially expressed in NLF-EVs of CRS patients versus HCs. In addition, eight miRNAs were differentially expressed in NLF-EVs of CRSwNP versus CRSsNP patients. The mucin-type O-glycan biosynthesis was a high-ranked predicted pathway in CRS patients versus healthy controls (HCs), and the Transforming growth factor beta (TGF-β) signaling pathway was a high-ranked predicted pathway in CRSwNP versus CRSsNP patients. We demonstrated the presence of and differences in NLF-EV miRNAs between CRS patients and HCs. These findings open up a broad and novel area of research on CRS pathophysiology as driven by miRNA cell communication.